Simultaneous Editing of Two Copies of Gh14-3-3d Confers Enhanced Transgene-Clean Plant Defense Against Verticillium dahliae in Allotetraploid Upland Cotton - Zhang, Zhennan; Ge, Xiaoyang; Luo, Xiaoli; Wang, Peng; Fan, Qiang; Hu, Guang; Xiao, Juanli; Li, Fuguang; Wu, Jiahe (Frontiers in Plant Science, 2018)
Gossypium hirsutum is an allotetraploid species, meaning that mutants that are difficult to generate by classical approaches due to gene redundancy. The CRISPR/Cas9 genome editing system is a robust and highly efficient tool for generating target gene mutants, by which the genes of interest may be functionally dissected and applied through genotype-to-phenotype approaches. In this study, the CRISPR/Cas9 genome editing system was developed in G. hirsutum through editing the Gh14-3-3d gene. In T0 transgenic plants, lots of insertions and deletions (indels) in Gh14-3-3d at the expected target site were detected in the allotetraploid cotton At or Dt subgenomes. The results of the PCR, T7EI digestion and sequencing analyses showed that the indels of Gh14-3-3d gene can be stably transmitted to the next generation. Additionally, the indels in the At and Dt subgenomes were segregated in the T1 transgenic plants following Mendelian law, independing on the T-DNA segregation. Two homozygous Gh14-3-3d-edited plants free of T-DNA were chosen by PCR and sequencing assays in the T1 plants, which were called transgene-clean editing plants and were designated ce1 and ce2. ce1 and ce2 in the T2 lines had high resistance to Verticillium dahliae infestation compared to the wild-type plants. Thus, the two transgene-clean edited lines can be used as a germplasm to breed disease-resistant cotton cultivars, possibly avoiding complex and expensive safety assessments of the transgenic plants.